Ethnobotanical study on the traditional uses of Rosmarinus officinalis L. in the Nâama Region (South-Western Algeria) - Aouissat , Hanane; Benabderrahmane, Mokhtar; Diaf, Mustapha (Ethnobotany Research and Applications, 2026)
Background: Rosmarinus officinalis L. (rosemary) is extensively used by indigenous communities in Algeria for a wide range of therapeutic purposes. Although rosemary holds important cultural and medicinal value, the Nâama region remains insufficiently documented in ethnobotanical literature. Methods: This study aims to document, analyse and evaluate local ethnobotanical knowledge regarding the traditional uses of R. officinalis within indigenous pharmacopeia. An ethnobotanical survey was conducted among 300 purposively selected informants using semi-structured questionnaires. Quantitative indices, including Use Value (UVs), informant Consensus Factor (ICF), Fidelity Level (FL) and Plant Part Value (PPV) were calculated. Advanced statistical analyses (Chi-square, ANOVA) were performed to assess the influence of socio-demographic factors on knowledge distribution. Results: The species demonstrated high ethnopharmacological relevance (UV = 3.46). Digestive (FL= 86 %, ICF = 0.992) and respiratory disorders (FL= 69.33%, ICF= 0.978%) were the ailments most frequently treated using rosemary. Leaves were the most commonly used plant part (PPV= 0.623). Infusion (62.33%) and decoction (36.33%) were the dominant preparation methods. Statistical comparisons revealed significant differences in knowledge transmission patterns between age groups and localities. Conclusions: These findings confirm the therapeutic and cultural significance of Rosmarinus officinalis L. and underscore the importance of further targeted phytochemical and pharmacological studies to support its safe integration into complementary and traditional medicine systems. The study provides a robust baseline for conservation efforts and public health policy recommendations. Keywords: Rosmarinus officinalis L., Nâama region, indigenous knowledge, traditional medicine, ethnobotanical survey.